2016
DOI: 10.1109/tthz.2016.2545519
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable 240–290 GHz Waveguide Enclosed 2-D Grid HBV Frequency Tripler

Abstract: This paper presents a high-power 240-290 GHz waveguide enclosed two-dimensional (2-D) grid heterostructure barrier varactor (HBV) frequency multiplier. A 35 mW of output power is produced at 247 GHz with an input power of 900 mW. The operational bandwidth is tunable within a 50 GHz span by the use of an input tuner able to adjust the input matching of the 2-D grid HBV frequency multiplier. Tuning is achieved by moving a suspended dielectric slab in the input waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…12) and can be made extremely compact in practice [65]. By spatially power combining 72 HBV diodes in a closed waveguide, Dahlbäck et al demonstrated the first tripler operating close to submillimeter-wave frequencies [23]. Large multidiode arrays can be analyzed and simplified via a unit-cell approach.…”
Section: B Alternative Hbv Circuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…12) and can be made extremely compact in practice [65]. By spatially power combining 72 HBV diodes in a closed waveguide, Dahlbäck et al demonstrated the first tripler operating close to submillimeter-wave frequencies [23]. Large multidiode arrays can be analyzed and simplified via a unit-cell approach.…”
Section: B Alternative Hbv Circuitsmentioning
confidence: 99%
“…In particular, the group at IEMN in Lille demonstrated the first HBV tripler with a conversion efficiency above 10% at 250 GHz [19]. Since 2000, the main achievements have involved integrated HBV circuits, with highpower triplers [20], quintuplers [21], and novel multiplier topologies being developed based on nonlinear transmission lines [22] and large HBV grids [23]. In this review paper, we present a historical overview, the basic concepts, and the current status of HBV multipliers for THz applications.…”
Section: Introductionmentioning
confidence: 99%
“…The paralleled unit cell modeling approach outlined in [5] was used in the design of a 1-W input power multiplier module. The varactor grid consists of 128 square unit cells organized into 8 rows and 16 columns, with the columns aligned with the E-field of the waveguide.…”
Section: Designmentioning
confidence: 99%
“…A good summary and discussion of grid multiplier design can be found in [2] and the quasi-optical equivalent in [3]. Other successful grid frequency multiplier demonstrators include an HBV grid with 684 mW of output power at 93 GHz [4] and 35 mW at 247 GHz [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been presented to prevent different resonances in the substrates [4] by enabling higher order mode excitation, diode yield, and instabilities to be accounted for. We verified our model by means of a 72 dipole coupled HBV frequency tripler array, which was designed using the unit cell method [6].…”
Section: Introductionmentioning
confidence: 99%